Pengaruh Metode Game Based Learning (GBL) terhadap Motivasi Belajar Siswa Pada Mata Pelajaran IPAS di Kelas IV SDIT Alam Darul Furqon: Pengaruh Metode Game-Based Learning (GBL) Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran IPAS - Rifza Irmada Yanti Irmada Yanti; Farida Ariani; Firda Khairati Amris; Joni Indra Wandi; Melda Delvia (Institut Agama Islam Sumatera Barat Pariaman, 2026)
This research is driven by observational data showing low student engagement characterized by lack of enthusiasm, drowsiness during learning, and noise in the classroom. This is caused by the inadequate implementation of appropriate learning methods by teachers. This study aims to determine the effect of the Game Based Learning (GBL) method on student learning motivation in science subjects for grade IV of SDIT Alam Darul Furqon. This study uses a quantitative approach with a one-group pretest-posttest design. The research sample consisted of 24 grade IV students taken from a total population of 119 students. Data collection techniques used questionnaires, while data analysis techniques included normality tests and hypothesis testing (t-test). The results of the statistical analysis showed a t-count value of 3.942 which was significantly greater than the t-table of 1.711. The significance value (2-tailed) obtained was 0.001, much smaller than the significance level of 0.05. Thus, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. These results prove that the Game Based Learning method has a significant influence in increasing the learning motivation of elementary school students.